Ascertaining Leadership Styles Of Defence Funded Schools - Sharma, Rahul (International Journal of Scientific Research and Management (IJSRM), 2016)
Educational Leadership is identified as an important factor for quality education. Successful leadership isnotthe result of simply obtaining a position, but rather possessing the knowledge and understanding ofsuccessful leadership skills along with the personal ability to effectively implement those skills. Hence, SchoolPrincipals need impressive skills to provide effective leadership in diverse school environments. Throughout theworld, education policy makers are constantly looking for ways to prepare school leaders to deal with thecomplex challenges facing public education in the 21st century. Research has demonstrated a clear correlationbetween effective school leadership and student achievement. The purpose of the study is to explore theleadership styles adopted by Principals of Defence funded Schools and highlight research issues in relation tooverall performance and Students achievementas conceptualized by Bolman and Deal’s Four-Frame Model ofLeadership (1991).